Panas pela of education: Desegregation of Muslim and Christian post-reconciliation at SMPN 4 Salahutu Liang and SMPN 9 Ambon - Anju Nofarof Hasudungan (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This article examines the process of desegregation through panas pela of education at SMPN 4 Salahutu Liang and SMPN 9 Ambon. Panas pela of education is a transformation of pela gandong local wisdom with the aim of overcoming segregation in schools. Pela gandong is a bond of brotherhood between the people of Maluku, regardless of religion, either Islam or Christian. The implementation of panas pela of education has been started since 2013 between SMPN 9 Ambon, whose students are 99% Christian/Catholic and SMPN 4 Salahutu Liang, which are 100% Muslim students. This research method uses qualitative research with a case study approach. Data collection techniques used by observation, participation, literature review, interviews, and documentation. Panas pela of education as a process of desegregation is carried out in the form of joint activities such as sports fairs, scouts, iftar, Christmas, student council activities and teacher exchanges. In addition, the students also performed dances, songs, and poetry without any segregation between them. In the midst of the current strengthening of polarization due to political choices, the panas pela of education is present as a means of social integration and evidence of the existence of harmonization between religious adherents in Indonesia.